Gabapentin-Induced Adrenal Insufficiency: The Hypothalamic-Pituitary-Adrenal Axis Stress Misresponse and Risk of Infection: A Case Report and Literature Review - Evmorfia Pechlivanidou; Alexandros Chatzikyriakos; Maria Anna Zisi; Nikolaos Paraskevopoulos; Semeli Kaltsa; Orestis K. Konstantas; Panteleimon Zogakis; Aikaterini Catsouli; Nick Sekouris; Rodanthi E. Margariti (MDPI AG, 2024)
This literature review, in light of the presented case report, explores the complex interplay between gabapentin (GBP), a gamma-aminobutyric acid (GABA) analog, and the hypothalamic-pituitary-adrenal (HPA) axis in patients undergoing major surgical procedures. It specifically investigates the potential impact of GBP on cortisol levels, stress responses, and infection risk, illustrated by a detailed clinical case. This review combines a comprehensive literature search with a case report of a 17-year-old male with osteosarcoma who experienced transient adrenal insufficiency and infections while receiving GBP. The case is analyzed in the context of the existing literature on GBP and the HPA axis. The findings highlight the intricate relationship between GBP use, adrenal insufficiency, and infection susceptibility. It underscores the need for further research and clinical vigilance when prescribing GBP to patients with underlying medical conditions, particularly in the context of major surgical procedures. The review underscores the need for further research and clinical vigilance when prescribing GBP, particularly in perioperative settings. In conclusion, GBP's effects on the HPA axis and immune responses are complex and multifaceted. Clinicians should exercise caution when prescribing GBP, especially for patients with underlying conditions undergoing major surgery. Further research is needed to elucidate the mechanisms of GBP's influence on cortisol levels and stress responses.